(untitled) (Prudentia Iuris, 2019)
Resumen: Una de las aspiraciones que la política criminal se encuentra llamada a concretar en pos de alcanzar el culmen de su misión es dotar de sustento a un Derecho Humano a la Seguridad más amplio. En clave con ello, ante un escenario delictivo multicausal y pluridimensional, debe abrirse a una lectura global de la conflictividad que posibilite medidas superadoras a problemáticas complejas. Es decir, respuestas integrales e integradoras de todas las franjas sociales expuestas a una inseguridad objetiva sin fronteras. Abstract: One of the aspirations that criminal policies are called to realize in order to achieve the highest level of its mission, is to provide a basis for a broader Human Right to Security. In tune with this, presented with a criminal scene that is multiple in its causes and dimensions, there must be a global approach to the conflict that allows for measures that address complex problems. This is, responses that are integral and integrate all people exposed to an objective, borderless state of insecurity.